A sudden shift: Students' perception of distance and online education in physical education amidst COVID-19 Pandemic - Lobo, Joseph (Edu Sportivo: Indonesian Journal of Physical Education, 2022)
Students' perception is critical because it provides essential information about the current benefits and challenges they are experiencing in the distance and online education setting. This study explores students' perception of physical education regarding the current educational environment in respect to gender, family accommodation, income, gadget, and source of internet connection. 262 1st year students taking minor PE are the participants in this study. Descriptive statistics such as frequency and percentage were utilized to describe the demographic characteristics of the respondents. At the same time, mean and standard deviation were used to describe students' attitudes towards distance and online education. Also, One-way ANOVA, Mann-Whitney U, and Kruskal Wallis H were utilized to determine the significant difference between groups regarding their perspective in the current educational setting. Based on the results, a statistically significant difference was found between groups concerning family accommodation. On the other hand, no difference was observed between groups of gender, income, gadget, and source of internet connection. In summary, most of the students positively perceived this current setting as beneficial to them. However, there are still challenges that pose threats to this current system. In this regard, the recommendation to address the challenges observed based on study findings and recommendations for future research is a result of this.